a-glukosi̇daz ve a-ami̇laz enzi̇mleri̇ni̇n, apis mellifera L. ve çam balından izolasyonu ve saflaştırılması ile bal olgunlaştırıcı enzi̇m akti̇vi̇teleri̇ni̇n tayi̇ni̇ içi̇n anali̇ti̇k yöntem geli̇şti̇ri̇lmesi̇ - Akyıldız, İsmail Emir (My University, 2023)
İnvertaz ve diastaz enzim aktiviteleri balın kalite göstergelerindendir. Bu enzimlerin aktivite tayininde yanlış pozitiflikler raporlayabilen, özel substratların enzimatik hidrolizine dayanan kolorimetrik teknikler kullanılmaktadır. Çalışmamızda, öncelikle bal ve hipofaringeal bezlerden (HPG) invertaz ve diastaz enzimlerinin izolasyonu ve saflaştırılması için yeni bir metodoloji geliştirilmesi hedeflenmiştir. Devamında, saf enzimlerin, HPLC ile balda diastaz/ invertaz aktivite ve yabancı enzim tayininde otantik referanslar olarak kullanılması amaçlanmıştır. Bu amaçla, HPG ve bal proteomu sıralı ultrafiltrasyon yaklaşımı ile izole edilmiştir. Sonrasında, hedef enzimler 3 adımlı saflaştırma protokolü ile MPLC’de saflaştırılmıştır. Devamında, saf enzimler yardımıyla HPLC sisteminde aktivite ve yabancı enzim tayin yöntemi geliştirilmiştir. Diastaz ve invertaz yeni izolasyon prosedürüyle sırasıyla 24,3 ve 9 kat zenginleştirilmiştir. Saflaştırma prosesinde, invertaz ham ekstrakta oranla 19,9 kat, diastaz ise 39,2 kat daha saf elde edilmiştir. Geliştirilen HPLC yönteminin validasyonunda, doğrusal (diastaz R2=0,994 ve invertaz R2=0,992), tekrarlanabilir ve tekrarüretilebilir (%RSD<2) aktivite sonuçları raporlanmıştır. LOD/ LOQ seviyeleri diastaz için 6,1-6,8 Schade U/ g ve invertaz için 28,1-31,6 U/ kg’dır. Kolorimetrik ve HPLC yöntemlerinin 15 örneği ait karşılaştırma analizinde, regresyon testi (R2>0,99), F testi (F=1,04/ 1,02) ve t testi (t=1,04/ 1,02) kabul edilebilir istatistiksel sonuçlar üretmiştir. Yeni yöntemle 107 örnekteki %41 oranında yabancı diastaz pozitifliği tespit edilebilmiştir. Yeni yöntem, aktivite tabanlı yöntemlere göre hızlı, tutarlı ve maliyetsiz olup, yabancı orijinli diastaz varlığını da ballarda eş zamanlı görüntüleyebilmektedir.

Invertase and diastase enzyme activities are among the quality indicators of honey. Colorimetric assays based on enzymatic hydrolysis of specific substrates are used to determine the activities of these enzymes and they may produce false positive results. Our study primarily aimed to develop a methodology for the isolation and purification of invertase and diastase in honey and hypopharyngeal glands (HPG). Subsequently, it was aimed to use these pure enzymes as authentic references in determination of diastase/ invertase activities and foreign enzymes in honey using HPLC. For this, HPG and honey proteome were isolated utilizing sequential ultrafiltration. Then, the target enzymes were purified on MPLC using 3-steps novel purification protocol. HPLC-based activity and foreign enzyme determination method was developed by employing pure enzymes. Diastase and invertase were enriched 24.3 and 9 fold, respectively, utilizing the isolation procedure. As a result of the purification, invertase, and diastase were 19.9 and 39.2 fold purer in comparison to crude extract. According to validation, linear (diastase R2=0.994 and invertase R2=0.992), repeatable and reproducible (%RSD<2) activity results were obtained. LOD/ LOQ levels were 6.1-6.8 Schade U/ g for diastase and 28.1-31.6 U/ kg for invertase. In comparison analyses between colorimetric and HPLC methods encompassing 15 samples, regression test (R2>0.99), F-test (F=1.04/ 1.02) and t-test (t=1,04/ 1.02) results were statistically acceptable. The 41% foreign diastase positivity percentage in 107 samples could be successfully reported with the new method. The novel method is fast, cost-effective, and accurate compared to activity-based assays, and foreign diastase adulteration can also be monitored simultaneously in honey.
Development of analytical method to determine honey elaborative enzyme activities via isolation and purification of a-glucosidase and a-amylase from apis mellifera L. and pine honey
Keywords: Bal; Diastaz; Enzim; Enzyme; Honey; HPLC; HPLC Diastase; Invertase; İnvertaz